The Effect of Infographic-Based Booklets on the Knowledge and Attitude Toward Unmet Need for Family Planning Among Women of Reproductive Age - Rena Fidia; Anik Purwati; Rosyidah Alfitri (Midwifery Department, Poltekkes Kemenkes Denpasar, Indonesia, 2026)
One of the reproductive health problems that can increase the risk of unwanted pregnancy is unmet need in the Family Planning (FP) program. Despite having the desire to delay or limit pregnancy, some women of reprpductive age in the Pujon Community Health Center, Malang Regency, still do not use contraceptive methods. This study aims to analyze the effect of infographic-based booklets as a counseling medium on the knowledge and attitudes of women of reproductive age (WRA) regarding unmet need. This study used a quasi-experimental design with a non-equivalent control group design. The research sample consisted of 28 respondents, divided into a control and an intervention group, with 14 respondents in each group. The sampling technique used was convenience sampling. Data were collected using questionnaires before and after the intervention, and analyzed using the Mann-Whitney test with a significance level of p < 0.05. The results showed that after the provision of infographic-based booklets, there were differences between the control and intervention groups in knowledge (p = 0.000) and attitudes (p= 0.050). Based on these results, it can be concluded that the infographic-based booklet is effective in increasing knowledge and forming positive attitudes of women of reproductive age regarding unmet needs.